Novel Aerogels Based on Citric Acid Crosslinked Bacterial Cellulose for Sustained Release of Nicotine in Oral Nicotine Products - Zhou Jian; Zhang Zhan; Ma Ke; Xu Yongming; Li Peng; Wang Yixuan (Contributions to Tobacco and Nicotine Research)
In this study we developed a novel carrier material that can be used to regulate nicotine release profile to provide a more constant release. Bacterial cellulose (BC) was produced by fermentation of tobacco waste, nicotine was derived from the backfilling of tobacco extracts. Citric acid (CA) has been used to react with bacterial cellulose to prepare an aerogel (CA-BC) which showed to possess sustained nicotine release by varying CA and its crosslinking ratio with BC. Aerogels prepared at 10% CA/BC ratios during crosslinking exhibited significant sustained nicotine release effects. Another notable finding was that the sustained-release of nicotine for the CA-BC aerogel with high nicotine contents significantly outperformed that of low nicotine contents. The Weibull model and Gallagher-Corrigan model were used to elucidate the mechanism of nicotine dissolution from CA-BC aerogels. Material characterization revealed that the CA-BC aerogel had an improved thermal stability and decreased water absorption, a 3D fiber network structure at the microscopic level with an optimal average pore size of 30 μm was used to explain this difference.